Pengaruh Kesadaran Wajib Pajak Terhadap Kepatuhan Wajib Pajak Bumi Dan Bangunan Di Kecamatan Tabir Induk Kabupaten Merangin - Kusuma, Rio nata; Anderson, Irzal; Sariani, Dona (Civic Education Perspective Journal, 2023)
This research is motivated by the problem of poor compliance among land taxpayers and community structures in the Tabir area of Merangin Regency. The purpose of this study is to determine the relationship between land and building taxpayer compliance in Tabir induk sub-district, Merangin district is influenced by the knowledge of land and building taxpayers. Quantitative methodology was used in this study, the data collection tool used a questionnaire. Quantitative research is a research method used to answer the truth of the hypothesis. The conclusion of this research data analysis shows that the taxpayer awareness variable (X) has an effect on land and building taxpayer compliance (Y). The coefficient of determination R, which is 38.9 percent, indicates the degree of impact between factors in the examination of taxpayer awareness and compliance among land and building taxpayers. It is hoped that the recommendations in this study will increase the sample size of the study, expand the sample of researchers, and allow researchers to conduct studies in other locations or provinces so that the findings can be extrapolated to a larger population. This research contributes to the creation of courses, especially in the field of taxpayer awareness and taxpayer compliance. In addition, researchers are expected to focus their studies on additional elements that may affect taxpayer compliance outcomes that have not been included in this study.